Upscaling a chemical screening approach to assess impacts of shale, tight and deep gas development on unconfined aquifers - Rebecca Doble; Dirk Mallants; Dennis Gonzalez; Yousef Beiraghdar Aghbelagh; Luk Peeters; Russell Crosbie; Sarah K Marshall; Tim Evans (Journal of Hydrology: Regional Studies, 2023)
Study region: Beetaloo Sub-basin (Northern Territory) and Cooper Basin (Queensland and South Australia), Australia. Study focus: A chemical screening approach was upscaled to regional scale to assess impacts of chemical spills on unconfined aquifers. Chemical dilution factors (DFs) were developed from hydrogeochemical modelling to predict the impact of hypothetical chemical spills as part of a hazard identification process from the potential development of shale, tight and deep gas in the Beetaloo Sub-basin and Cooper Basin. Advection and dispersion modelling (non-reactive HYDRUS 1-D) was used as a conservative screening approach to estimate DFs vertically through the unsaturated zone and laterally through the unconfined aquifers. The results were upscaled to basin scale, based on spatially distributed soil, groundwater and aquifer information, including the presence of karsts. The spatial approach successfully defined areas that required additional assessment prior to any future development. New hydrological insights for the region: For chemical concentrations from surface spills to not exceed ecotoxicological thresholds at the water table, a DF of > 1000 was required. Screening areas with a DF of > 1000 constrained the area of concern for aquifer contamination from spills to 0.3 % and 14 % of the Beetaloo and Cooper regions respectively. The likelihood for long term impacts from potential undetected chemical leaks on groundwater dependent ecosystems was assessed to < 0.1 % of the Cooper region due to dilution in lateral groundwater flow, but 18 % of the Beetaloo region.